Development and evaluation of a composite dosage form containing desmopressin acetate for buccal administration - Dina Kottke; Bjoern B. Burckhardt; Tanja C. Knaab; Jörg Breitkreutz; Björn Fischer (Elsevier, 2021)
Desmopressin acetate (DDAVP) is an oligopeptide indicated for the treatment of primary nocturnal enuresis, for example. The poor oral bioavailability of DDAVP accelerated a shift to alternative routes of administration like nasal and oromucosal, whereby nasal administration results in high fluctuations increasing the risk of undesirable side effects. Aim of the study was to use a new composite dosage form (solid matrix attached to a bilayer mucoadhesive film) to make DDAVP available via oromucosal route, reducing the risk of undesirable side effects through precise dosing. DDAVP was incorporated into a solid matrix in the form of a minitablet, and both direct tableting (AV > 30) and granulation followed by tableting (AV = 17.86) were compared. Minitablets with content uniformity could only be obtained by granulation and loss supplementation (AV = 11.27) with immediate drug release (>80% after 7-8 min) and rapid disintegration (<49 s). Permeation studies were performed with a clinically relevant dose (200 μg) in a time interval of up to one hour, resulting in apparent permeation coefficients of 4.90 × 10−6 cm/s (minitablet) and 2.04 × 10−6 cm/s (composite). Comparable fluctuations showed no inferiority of composite and minitablet regarding dosing accuracy. Thus, a step towards controlled and dose-accurate transmucosal delivery of systemically active DDAVP could be achieved.